2018
DOI: 10.1161/circulationaha.117.028782
|View full text |Cite|
|
Sign up to set email alerts
|

Angiography Versus Hemodynamics to Predict the Natural History of Coronary Stenoses

Abstract: URL: https://clinicaltrials.gov. Unique identifier: NCT01132495.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…The reproducibility of these assessments is good, and similar to that reported in previous QFR studies. 3. Findings of pathological QFR are not rare (7.7% of all vessels measured) and are more frequent in the LAD than in LCX and RCA.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The reproducibility of these assessments is good, and similar to that reported in previous QFR studies. 3. Findings of pathological QFR are not rare (7.7% of all vessels measured) and are more frequent in the LAD than in LCX and RCA.…”
Section: Discussionmentioning
confidence: 96%
“…Invasive methods to assess the hemodynamic significance of coronary artery stenoses are associated with improved short-and long-term outcomes, principally driven by a reduced incidence of revascularization and target vessel myocardial infarction [1][2][3]. Despite their advantages, the penetration of these invasive techniques remains low due to cost or logistic considerations, limited access, and a perceived increased risk associated with intracoronary procedures and the administration of vasodilators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, iFR-controlled stent implantation is recommended for stenoses with narrowing of the lumen at the range of 40-90% and the values of the iFR < 0.89, or FFR < 0.80. The Fractional Flow Reserve Versus Angiography for Multivessel Evaluation 2 (FAME2) study confirmed better efficacy of FFR (iFR) -guided PCI as compared to only optimal medical treatment (OMT) (hazard ratio (HR) 0.32 [95% confidence interval (CI) 0.19-0.53; p < 0.001]) [9][10][11]. In Ukraine, FFR/iFR-guided PCI is performed in the Institute of Car Adopted from Davies JE et al [14].…”
Section: Introductionmentioning
confidence: 98%
“…In a study published in 2007, 8 in 250 patients (452 lesions) assessed by FFR before PCI, 32% of the lesions had their initially planned treatment strategy modified after FFR measurement, which is a major change because it would imply inadequate treatment in more than one third of the patients. More recently, Ciccarelli et al 9 in a FAME 2 substudy, analyzed the value of angiography compared to FFR to predict the natural history of coronary lesions, correlating MCAE index with the angiographic and physiological importance of these lesions in patients (n = 607) who were initially left only on drug treatment. In the subgroups in which FFR was discordant of angiography (FFR > 0.80 and SD ≥ 50% or FFR ≤ 0.80 and SD < 50%), clinical progression was worse in those in whom FFR was ≤ 0, 80, even if the lesion was not significant, and benign in those in whom FFR was > 0.80, regardless of SD.…”
mentioning
confidence: 99%